Vertebral vascular canal dysplasia in cats: signalment, CT and MRI characteristics, and prevalence - Van Koulil, Q.; Santifort, K. M.; Willems, D. S.; Bolen, G.; De Decker, S.; Bernardini, M.; Bergknut, N.; Van Soens, I. (Frontiers in Veterinary Science, 2025)
IntroductionNumerous vertebral anomalies have been characterised in dogs, whereas congenital vertebral malformations in cats have been less frequently described. The aim of the present study was to report and describe a vertebral malformation in cats recently reported in dogs—vertebral vascular canal dysplasia (VVCD)—to apply the previously reported scoring system to a feline study population, and to evaluate its inter- and intra-observer agreement.Material and methodsCT and MRI studies from five different feline populations were retrospectively evaluated. Patients were included as VVCD-affected if they showed single or multiple VVCDs of the thoracic vertebral column and were scored using the previously published canine scoring system.ResultsA total of 2,037 cats were evaluated, of which 541 (26.6%) were found to have VVCD. In addition to the thoracic vertebrae, cervical and lumbar vertebrae were also affected. Different score distributions were observed across thoracic vertebrae, suggesting a possible regional pattern. Most patients underwent CT (508), while only 33 had MRI.DiscussionCT was considered superior due to its higher spatial resolution and the availability of axial/transverse images for all vertebral bodies, which allowed improved visualisation of vertebral body anatomy and better evaluation of the form, shape, and depth of the dysplastic vascular canals. Especially in more subtle cases, transverse views were necessary to confirm the presence and assess the extent of VVCD. Intra- and interobserver agreement was variable (range 0.543-1.000 and 0.225-0.894, respectively) depending on adjustments to the scoring system, reflecting the role of subjectivity in the interpretation of VVCD with this system. Clinical relevance was not assessed. Future studies are required to investigate prevalence, explore possible etiologies, and determine the potential clinical significance of VVCD in feline spinal disease.